The chemistry of polymers - Nicholson, John W. (Royal Society of Chemistry, 2017)
A highly readable introductory textbook on polymer science, ideal for those requiring a broad overview of the subject. Recent advances on special topics in polymer chemistry and polymers and the environment are included.